A Cowboy Christmas Legend - Broday, Linda (Naperville, Illinois : Sourcebooks Casablanca, 2021)
Devastated by grief, Texas Ranger Sam Legend II tries to make a new start in the Texas Panhandle. As a bladesmith, all he needs is a bed, a hot fire, and enough solitude to let him heal after the death of his wife. But when fiery Cheyenne Ronan comes blasting into his shelter with accusations, he knows he wont be getting the peace he desires. From the moment he meets Cheyenne Ronan, Sams quiet life is anything but. Now hes hunting the men responsible for his wifes murder, tracking down a counterfeiting ring with the Texas Rangers, and caring for a family who finds refuge at her ranch. And with Christmas right around the corner, Sams got his hands full. But with Cheyenne by his side, hes starting to wonder whether a second chance could be the stuff of Legend.
Keywords: Texas Rangers -- Fiction; Widowers -- Fiction; Murder -- Investigation; Fiction; Historical western -- Fiction; Man-woman relationships -- Fiction; Christmas fiction; Romance fiction